Chemoradiotherapy followed by durvalumab in patients with unresectable advanced non‐small cell lung cancer: Management of adverse events - Yu Miura; Atsuto Mouri; Kyoichi Kaira; Ou Yamaguchi; Ayako Shiono; Kosuke Hashimoto; Fuyumi Nishihara; Shun Shinomiya; Tomoe Akagami; Yoshitake Murayama; Takanori Abe; Shin‐ei Noda; et al. (Thoracic Cancer)
Background Chemoradiotherapy followed by durvalumab is the standard treatment for the patients with local advanced non‐small cell lung cancer (NSCLC). There is a real‐world data about the management of adverse events, such as pneumonitis, according to the different institutions. Here, we present the experience regarding the management of adverse events after the initiation of durvalumab as daily practice. Methods From July 2018 to August 2019, 41 patients with locally advanced NSCLC, who underwent chemoradiotherapy followed by durvalumab, were retrospectively analyzed in the study using our medical records. Results The median age of patients was 72 years (range: 51–80 years). A total of 33 patients were male and eight were female, and 40 patients (98%) received a total radiation dose of 60 Gy as concomitant chemoradiotherapy. The median V20 for the entire cohort was 18.9% (range: 3.5–29.9). Any adverse events during chemoradiotherapy and durvalumab were observed in 32 patients (78.0%), while three patients (7.3%) experienced grade 3 toxicities. In total, 25 (61.0%) patients experienced pneumonitis, four (9.8%) thyroid dysfunction, three (7.3%) myopathy, two (4.9%) rash or eruption, one (2.4%) bowel disease and one (2.4%) malaise. Grade 3 pneumonitis, thyroid dysfunction and myopathy were observed in one (2.4%), one (2.4%) and one (2.4%), respectively. A total of 22 (53.7%) patients were unable to continue durvalumab due to pneumonitis. However, durvalumab was finally readministered to six patients. Conclusions The adherence to lung dose constraints such as V20 as well as close treatment monitoring are a prerequisite for the management of pneumonitis during maintenance therapy with durvalumab.